Translating from English into Indonesian: Which techniques to teach EFL students to be professional translators? - Faisal Mustafa; Mohammad Kholid (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
The credits for translation courses offered at the study program of English Language Teaching at a university level in Indonesia are very limited, which is not sufficient to teach and facilitate practices for all techniques of translation. Therefore, the students should only be taught techniques frequently used in translation from English to Indonesian. This research was to analyze translation techniques commonly used in translating from English to Indonesian. The data were collected from Colors magazine, an in-flight magazine for Garuda Indonesia. The magazine comes in two languages. The sentences were extracted, and translated sentences in Indonesian were compared to the original version in English. The research results showed that the most frequently used techniques in translating from English into Indonesian are amplification (23.36%), reduction (15.20%), transposition (12.32%), borrowing (12%), modulation (11.68%), and literal translation (10.08%). Therefore, it is recommended that lecturers teaching students majoring English Language Teaching provide them with those techniques of translations with practices, feedbacks and explicit instruction for revisions.